Digital religion and Generation Z: an empirical study in the context of China - Liu, Zhi; Ghouri, Arsalan Mujahid; Wang, Jing; Lin, Changqing (Frontiers in Psychology, 2025)
IntroductionThis study investigates the intersection of digital media and religious behavior among Chinese Generation Z, extending the Theory of Planned Behavior (TPB) by incorporating media content innovation and empathic willingness. It explores how platforms like Weibo and TikTok shape religious intentions and behaviors through visual and interactive features.MethodsA cross-sectional study was conducted with 534 Chinese Generation Z participants. Data were collected via surveys assessing the influence of media content innovation and empathic willingness on digital religious behavior, using the TPB framework. Structural equation modeling analyzed the relationships between these factors and religious intentions.ResultsFindings indicate that media content innovation and empathic willingness significantly enhance digital religious behavior within the TPB framework. Vibrant, emotionally resonant content on social media platforms fosters emotional engagement and active participation, amplifying religious intentions among participants.DiscussionThese results highlight social media’s transformative role in redefining religious practices among Chinese Generation Z. Media content innovation and empathic willingness emerge as critical drivers of engagement. The findings offer insights for religious organizations, policymakers, and social media platforms to foster meaningful cultural and religious interactions. This study underscores the need for tailored digital strategies to promote spiritual engagement in the digital age.